Social representations regarding psychoactive substances from an ethnic - racial and gender approach. Exploratory study, Universidad del Valle, Colombia - Blanco-Echeverry, María del Pilar (Prospectiva. Revista de Trabajo Social e Intervención Social, 2017)
The article is the product of a research on the trends of consumption and social representations (RS) regarding Psychoactive Substances (SPA) by students from the Northern Cauca (NC) Universidad del Valle, Colombia. The research was conducted with 298 students - women and men. A survey allowed to characterize the consumption of SPA in the university campus. The qualitative tools allowed to capture perceptions and images regarding the consumption of SPA. Although it is true that this group of students do not represent all the young people of the NC, the findings gave interesting clues to understand the consumption of SPA from the social representations built from their status as male, female, afro-descendant or indigenous, projecting in the differential discourses captured throughout the research. Looks of great utility to propose to the future differentiated strategies of intervention that allow a real inclusion in the processes of prevention and mitigation of the consumption.